Pré-condicionamento com ternatina no infarto do miocárdio induzido por isoproterenol em ratos - Leão Filho, Carmelo Silveira Carneiro (2011)
Acute myocardial infarction (AMI) is one of the most common causes of death in our country. As population ages, such illness have its prevalence rates increased. In order to analyse drug effects over myocardial lesions as a result of AMI, the myocardial infarction induction model by means of the administration of isoproterenol in rats is one of the most used at all, given the capability of that substance of mimicking the myocardial injury observed in humans. In the present study, preconditioning with intra-peritoneal ternatin, at a dose of 1 mg/kg was used. Fourteen consecutive days were assessed in the isoproterenol-induced MI (120 mg/kg) in Wistar rats. Myocardial lesions induced by isoproterenol was indicated by the rise in biochemical markers levels, such as SGOT (serum glutamic oxaloacetic transaminase) and troponin I, reduction in the activity of catalase enzyme in the myocardial tissue, as well as by histopathological changes assessed in the apex of the left ventricle. It was also evaluated mortality rates, hemoglobin and SGPT (serum glutamic pyruvic transaminase) serum concentrations, leukocytes, neutrophils counts and renal function. Preconditioning with ternatin unveiled protective effects within the myocardial infarction induced by isoproterenol in rats, once it diminished mortality rates, attenuated SGOT and troponin I concentrations, preserved catalase levels in the myocardium and diminished histopathological changes in the apex of the left ventricle Possible pathways accountable for such good results, reducing the degree of myocardial injury in this experimental essay, might be related to the antioxidant properties attributable to ternatin.